The Effect of Work Stress and Work Culture on Employee Performance at PPSDM of the Ministry of Villages, Development of Disadvantaged Regions, with Job Satisfaction as a Mediating Variable - Ghama Zaffrullah; Zainul Kisman (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2026)
This study examines the effects of work stress and work culture on employee performance with job satisfaction as a mediating variable at the Center for Human Resource Development (PPSDM), Ministry of Villages, Development of Disadvantaged Regions. Using a quantitative approach, data were collected from 75 employees and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The measurement model demonstrates adequate validity and reliability. The structural model results indicate that work stress has a negative and significant effect on job satisfaction, while work culture has a positive and significant effect on job satisfaction. Work stress does not have a significant direct effect on employee performance, whereas work culture and job satisfaction have positive and significant effects on employee performance. Mediation analysis reveals that job satisfaction fully mediates the relationship between work stress and employee performance and partially mediates the relationship between work culture and employee performance. These findings highlight the importance of strengthening work culture and maintaining job satisfaction to sustain employee performance in a public sector organization undergoing organizational transformation.